Social policy review 30 : analysis and debate in social policy 2018 (Social Policy Review Ser., 2018)
This book examines critical debates in social policy, including discussions on modern slavery, welfare chauvinism and the Grenfell Tower fire, to offer an informed review of the best in social policy scholarship over the past year.